Preparation of a NPTS@PANI composite material and its application in photocatalytic reduction of Cr(VI)
By in situ coating polyaniline on the NPTS surface to form NPTS@PANI composites, the problem of low reduction efficiency of existing photocatalysts Cr(VI) is solved, and efficient and stable Cr(VI) reduction performance is achieved, especially NPTS@ PANI-15 can completely reduce 100 mg/L of Cr(VI) within 10 minutes and remain efficient in various environments, significantly better than commercially available P25.
Patent Information
- Application Number
- CN202211395443.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-11-09
AI Technical Summary
The existing photocatalysts have low efficiency in the Cr(VI) reduction process, especially the poor Cr(VI) reduction performance of commercially available P25, which is difficult to meet the needs of industrial wastewater treatment.
Using a preparation method of composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI, the NPTS@PANI composite material is formed by coating polyaniline (PANI) in situ on the surface of NPTS, and used for photocatalytic reduction. Cr(VI). The process includes reacting tin tetrachloride pentahydrate, nickel chloride hexahydrate, selenium powder and o-phenanthroline in aqueous dimethylamine to prepare NPTS, followed by grinding in an acidic solution and reacting with aniline and ammonium persulfate, A red suspension was formed, and the NPTS@PANI composite was obtained by stirring and drying after an ice bath.
NPTS@PANI-15 can completely reduce 100mg/L of Cr(VI) within 10 minutes. Its Cr(VI) reduction performance is 90 times worse than that of commercially available P25, and under different environments (such as tap water, lake water, and sunlight ) showed high efficiency and stability, and the cycle tests remained efficient for 5 times.
Smart Images

Figure CN118045632B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of a NPTS@PANI-x (x=15, 50, 100) composite material and the photocatalytic reduction performance of Cr(VI) thereof, and belongs to the field of composite material preparation and photocatalysis. Background Art
[0002] The rapid development of modern industry has generated a large amount of industrial wastewater. Improper treatment of these wastewaters will cause serious ecological and environmental problems. Among them, industrial wastewater generated by leather tanning, textile and steel manufacturing industries usually contains typical heavy metal chromium pollutants, which exist in the form of Cr(VI) oxyacid ions and Cr(III) ions. Cr(VI) oxyacid ions are considered to be a carcinogen due to their acute toxicity to organisms, and they have high mobility in acidic and alkaline water bodies. Cr(III) ions are essential trace elements for the human body, and they can precipitate in alkaline water bodies. Therefore, reducing Cr(VI) to Cr(III) is considered to be an effective method for treating chromium-containing wastewater. At present, people have developed a variety of methods for the reduction of Cr(VI), and the main methods include: microbial reduction, chemical reduction and photocatalytic reduction. Among them, the photocatalytic reduction method has the advantages of low cost, simple operation and environmental friendliness, and is considered to be a promising Cr(VI) treatment method. During the photocatalytic reaction, the photocatalyst absorbs photons and generates photogenerated electrons and holes, which in turn generate a variety of reactive oxygen free radicals, among which the photogenerated electrons and reactive oxygen free radicals can reduce the highly toxic Cr(VI) to the less toxic Cr(III). Obviously, the photocatalytic activity of the photocatalyst is an important factor affecting the efficiency of the photocatalytic reduction of Cr(VI). Therefore, the development of highly active photocatalysts is of great significance for achieving efficient photocatalytic reduction of Cr(VI). Summary of the invention
[0003] The technical problem solved by the present invention is to propose a preparation method and application of NPTS@PANI composite material obtained by compounding NPTS with polyaniline, and the obtained material exhibits excellent performance in photocatalytic reduction of Cr(VI). Compared with NPTS@PANI-15, the Cr(VI) reduction performance of commercially available P25 is 90 times worse.
[0004] In order to solve the technical problem of the present invention, the proposed technical solution is: a preparation method of a composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI, the steps are as follows:
[0005] (1) adding tin tetrachloride pentahydrate, nickel chloride hexahydrate, selenium powder, and o-phenanthroline to a mixed solution of dimethylamine aqueous solution and ultrapure water, and transferring the mixture to a reaction kettle for heating, cooling, washing, and drying to prepare [Ni(phen)3][Sn3Se7]·1.5H2O (named as NPTS), and grinding the mixture for later use;
[0006] (2) crystalline powder NPTS is dispersed in an acidic aqueous solution and stirred evenly, which is recorded as dispersion A;
[0007] (3) dissolving aniline in an acidic aqueous solution and stirring the solution uniformly, which is referred to as solution B;
[0008] (4) Slowly pour dispersion A into solution B to form a red suspension C;
[0009] (5) Pour ammonium persulfate into the acidic aqueous solution, dissolve it by ultrasonication, and then pour it into the above red suspension C;
[0010] (6) After pouring, the suspension is placed in an ice-water mixture and stirred in an ice bath; after centrifugation, washing, and drying, the composite material NPTS@PANI is obtained.
[0011] Preferably, the synthesis method of NPTS in step (1) is: adding SnCl4·5H2O (0.51mmol, 0.178g), NiCl2·6H2O (0.52mmol, 0.124g), Se (2.10mmol, 0.166g) and o-phenanthroline (1.54mmol, 0.278g) to a mixed solution of dimethylamine aqueous solution (3mL, 40%wt) and H2O (1mL); sealing the mixture in a 25mL reactor and reacting at 190°C for 5 days; cooling to room temperature, washing the product with ethanol and water for multiple times and drying to obtain dark red block crystals of NPTS;
[0012] Preferably, the grinding method of the NPTS powder in step (1) is: take 0.05 g of NPTS crystals, add 2 mL of anhydrous ethanol, and grind until the anhydrous ethanol is completely volatilized.
[0013] Preferably, aniline monomer is used as a precursor and ammonium persulfate is used as an oxidant to in-situ coat polyaniline (PANI) on the surface of NPTS, and the pH value of the acidic solution used in the composite process is 2.5.
[0014] Preferably, the specific steps of in-situ coating of polyaniline are as follows:
[0015] (1) Pour 0.2 g of NPTS powder into 30 mL of ultrapure water, adjust the pH to 2.5 with hydrochloric acid solution, and stir for 10 min to obtain dispersion A;
[0016] (2) Pour a certain amount of aniline into 10 mL of ultrapure water, adjust the pH to 2.5 with hydrochloric acid solution, and stir for 10 min to obtain solution B;
[0017] (3) Slowly pour dispersion A into solution B and continue stirring for 30 min to obtain a red suspension C;
[0018] (4) Take a certain amount of ammonium persulfate and dissolve it in 30 mL of hydrochloric acid solution (pH = 2.5);
[0019] (5) 30 mL of ammonium persulfate solution was poured into the red suspension C at a flow rate of 0.4 mL / min using an intelligent syringe. The entire reaction system was placed in an ice bath and reacted for 10 h. After centrifugation, the suspension was washed twice with ultrapure water and anhydrous ethanol in sequence and dried in a vacuum oven at room temperature for 12 h to obtain brown powder NPTS@PANI.
[0020] Preferably, the dosage of aniline is 15 μL, 50 μL, and 100 μL, respectively, and the corresponding products are NPTS@PANI-x (x=15, 50, 100); the dosage of ammonium persulfate required for the above three products is 0.076 mg, 0.253 mg, and 0.506 mg, respectively.
[0021] In order to solve the technical problem of the present invention, another technical solution is proposed: a method in which the composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI is used for photocatalytic reduction of Cr(VI), and the pretreated composite material NPTS@PANI-x (x=15, 50, 100) is used for photocatalytic reduction of Cr(VI).
[0022] Preferably, the pretreatment process is: taking 50 mg NPTS@PANI-x (x=15, 50, 100) and adding it into 50 mL ultrapure water with pH=2.0 and stirring for 30 min.
[0023] Preferably, 50 mg of the pretreated material NPTS@PANI-x (x=15, 50, 100) is used for photocatalytic reduction of K2Cr2O7 solution at pH=3, and the K2Cr2O7 concentration is 100 mg / L.
[0024] Beneficial Effects
[0025] The present invention discloses a preparation method of a composite material based on organic hybrid metal selenide and polyaniline and its photocatalytic reduction performance of Cr(VI), belonging to the field of composite material preparation and photocatalytic application. The present invention obtains a composite material NPTS@PANI-15 by compounding polyaniline on the surface of NPTS. When pH=3, NPTS@PANI-15 can completely reduce 100 mg / L of Cr(VI) within 10 minutes. In addition, the material still has efficient catalytic ability in tap water, lake water, river water and sunlight environment. In 5 cycle tests, NPTS@PANI-15 showed high cycle stability.
[0026] At pH=3, NPTS@PANI-15 can completely reduce 100mg / L Cr(VI) within 10 minutes. The photocatalytic activity of NPTS crystals is low, and about 15% of Cr(VI) has not been reduced after 30 minutes of illumination. The reduction rate of Cr(VI) by NPTS@PANI-50 within 30 minutes reaches 99.4%, while the reduction rate of Cr(VI) by NPTS@PANI-100 within 30 minutes is 86.7%. By comparing with the commercially available P25, the catalyst concentration used is 1g / L. When reducing 100mg / L Cr(VI), P25 can only reduce to 10% within 10 minutes. Compared with NPTS@PANI-15, the Cr(VI) reduction performance of P25 is 90 times worse. Compared with the catalyst CdS@ZnIn2S4 reported in the literature, the performance of NPTS@PANI-15 is 6 times that of CdS@ZnIn2S4.
[0027] This product exhibits high catalytic activity for Cr(VI) in an acidic environment, and has a high adsorption capacity for Cr(VI) oxygen-containing acid ions; the composite of NPTS and PANI-15 effectively improves the separation efficiency of photogenerated electrons and holes, and improves its catalytic activity and cycle stability. The process of photocatalytic reduction of Cr(VI) by this product is dominated by photogenerated electrons, and the generated photogenerated electrons can effectively reduce Cr(VI) to Cr(III). BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described below in conjunction with the accompanying drawings.
[0029] Figure 1 PXRD spectra of the NPTS@PANI-x (x=15, 50, 100) composite materials obtained in Example 1.
[0030] Figure 2The SEM and TEM images of the NPTS@PANI-x (x=15, 50, 100) composites obtained in Example 1. Figures (a), (b), (c) and (d) are SEM images of NPTS, NPTS@PANI-15, NPTS@PANI-50 and NPTS@PANI-100, and Figures (e) and (f) are TEM images of NPTS and NPTS@PANI-15.
[0031] Figure 3 This is the fluorescence image of the NPTS@PANI-x (x=15, 50, 100) composite material obtained in Example 1.
[0032] Figure 4 This is the infrared image of the NPTS@PANI-x (x=15, 50, 100) composite material and PANI obtained in Example 1.
[0033] Figure 5 This is the photocurrent diagram of the NPTS@PANI-x (x=15, 50, 100) composite material obtained in Example 1.
[0034] Figure 6 This is a curve diagram of the photocatalytic reduction of Cr(VI) by NPTS@PANI-x (x=15, 50, 100) in an acidic environment (pH=3) in Example 3.
[0035] Figure 7 This is a curve diagram of the photocatalytic reduction of Cr(VI) by NPTS@PANI-15 in different acidic and alkaline environments (pH=2, 3, 5, 7 and 9) of Example 4.
[0036] Figure 8 This is the photocatalytic reduction curve of NPTS@PANI-15 to different concentrations (50, 100, 150, 200 and 300 mg / L) of Cr(VI) in an acidic environment (pH=3) in Example 5.
[0037] Fig. 9 This is a bar graph of the photocatalytic reduction efficiency of Cr(VI) based on different NPTS@PANI-15 dosages (10, 50, 100 mg) in an acidic environment (pH=3) according to Example 6.
[0038] Fig.10 This is the photocatalytic reduction curve of Cr(VI) by NPTS@PANI-15 in 5 cycle tests in Example 7.
[0039] Fig.11 This is the PXRD spectrum of NPTS@PANI-15 before and after the cyclic reaction in the 5-cycle test of Example 7.
[0040] Fig.12 This is the photocatalytic reduction curve of NPTS@PANI-15 to an acidic (pH=3) Cr(VI) solution (100 mg / L) in tap water, Nanjing Xuanwu Lake water, and Nanjing Yangtze River water environment in Example 8.
[0041] Fig.13 This is the photocatalytic reduction curve of NPTS@PANI-15 to an acidic (pH=3) Cr(VI) solution (100 mg / L) under sunlight conditions in Example 9. DETAILED DESCRIPTION
[0042] Embodiment 1:
[0043] Synthesis of NPTS@PANI:
[0044] SnCl4·5H2O (0.51mmol, 0.178g), NiCl2·6H2O (0.52mmol, 0.124g), Se (2.10mmol, 0.166g) and o-phenanthroline (1.54mmol, 0.278g) were added to a mixed solution of dimethylamine aqueous solution (3mL, 40%wt) and H2O (1mL). The mixture was sealed in a 25mL reactor and reacted at 190°C for 5 days. After cooling to room temperature, the product was washed with ethanol and water several times and dried to obtain dark red block crystals. 0.05g of NPTS crystals were taken each time, 2mL of anhydrous ethanol was added and ground until the anhydrous ethanol was completely evaporated. 0.2g of NPTS powder was poured into a beaker, 30mL of ultrapure water was added, the pH was adjusted to 2.5 with hydrochloric acid solution, and stirred for 10min to obtain dispersion A. Take 15μL, 50μL, and 100μL of aniline respectively and pour them into 10mL of ultrapure water, adjust the pH to 2.5 with hydrochloric acid solution, and stir for 10 minutes to obtain solution B. Slowly pour dispersion A into solution B, continue stirring for 30 minutes to obtain red suspension C. Dissolve 0.076mg, 0.253mg, and 0.506mg of ammonium persulfate (APS) in 30mL of ultrapure water, and adjust the pH to 2.5 with hydrochloric acid solution. Use an intelligent syringe to drop 30mL of ammonium persulfate solution into the red suspension C at a flow rate of 0.4mL / min. The entire reaction system is placed in an ice bath, reacts for 10 hours, centrifuged, and washed twice with ultrapure water and anhydrous ethanol in turn. Dry in a vacuum drying oven at room temperature for 12 hours to obtain powders named NPTS@PANI-15, NPTS@PANI-50, and NPTS@PANI-100. From Figure 3It can be seen from the fluorescence spectrum that the recombination of photogenerated electron-hole pairs is also a key factor affecting the photocatalytic reduction of hexavalent chromium. The recombination of electrons and holes can be judged by comparing the photoluminescence intensity of the catalyst. Therefore, we conducted photoluminescence spectrum tests on the prepared catalysts NPTS, NPTS@PANI-15, NPTS@PANI-50 and NPTS@PANI-100. Using 470nm excitation light, the main emission peaks of these four materials are located at 708nm. As can be seen from the figure, the NPTS crystal has the highest emission peak intensity, indicating that the intrinsic sample of the crystal has a high recombination rate of electrons and holes. In contrast, NPTS@PANI-15, NPTS@PANI-50 and NPTS@PANI-100 have relatively low photoluminescence intensities, indicating that the recombination rate of photogenerated electrons and holes is reduced. Among them, NPTS@PANI-15 has the lowest photoluminescence intensity, indicating that its recombination rate of photogenerated electrons and holes is the lowest, which is beneficial to its photocatalytic reduction of hexavalent chromium. From Figure 4 In order to verify whether polyaniline is successfully loaded on the surface of NPTS crystal, we characterized the prepared NPTS crystal, PANI, NPTS@PANI-15, NPTS@PANI-50 and NPTS@PANI-100 by Fourier transform infrared spectroscopy. Figure 4 As shown in Figure 2, compared with NPTS, PANI, NPTS@PANI-15, NPTS@PANI-50, and NPTS@PANI-100 are all at 796 cm -1 The absorption peak at 796 cm-1 is shown, which corresponds to the out-of-plane deformation vibration of NH on the benzene ring of polyaniline, indicating that PANI is successfully loaded on the surface of NPTS crystal. -1 The absorption peak intensity at gradually increases. Figure 5 The photocurrent graph can be obtained, and the transient photocurrent response of the test material is also a method to determine the mobility of photogenerated carriers. Figure 5 As shown, we conducted transient photocurrent response tests on NPTS, NPTS@PANI-15, NPTS@PANI-50 and NPTS@PANI-100. They can all generate stable photocurrents under visible light irradiation (λ≥420nm). As can be seen from the figure, the photocurrent density of NPTS@PANI-15 is higher than that of NPTS, NPTS@PANI-50 and NPTS@PANI-100. This shows that NPTS@PAN-15 has the highest photogenerated electron-hole pair separation efficiency. Among them, the photocurrent density of crystalline NPTS is higher than that of NPTS@PANI-50 and NPTS@PANI-100.
[0045] Embodiment 2:
[0046] Photocatalytic experimental steps:
[0047] Take 50 mg of NPTS@PANI-x (x=15, 50, 100) prepared in Example 1 and add it to 50 mL ultrapure water at pH=2.0 and stir for 30 min. Centrifuge and set aside. Prepare a Cr(VI) solution with a concentration of 100 mg / L using K2Cr2O7, measure 50 mL of the Cr(VI) solution and add it to a 250 mL quartz reactor, and pour in the pretreated catalyst. Stir for 30 min under light-proof conditions to achieve adsorption-desorption equilibrium. Then turn on the xenon lamp equipped with a 420 nm filter and illuminate the suspension. During the irradiation period, take 2 mL of the suspension every 5 minutes, take out the supernatant by centrifugation (12000 rpm, 2 min) to test the residual Cr(VI) content, and pour the remaining liquid back into the reaction container. Analyze the absorbance of the supernatant with a UV-visible spectrophotometer.
[0048] The concentration of Cr(VI) was analyzed and determined by diphenylcarbazide spectrophotometry. The specific process is as follows: take 1 mL of supernatant, add 0.5 mL of 50% sulfuric acid and 0.5 mL of 50% phosphoric acid, then add 2 mL of color developer, mix well and immediately test on a UV-visible spectrophotometer. The color developer preparation method is as follows: weigh 0.5 g of diphenylcarbazide and dissolve it in 125 mL of acetone solution, perform ultrasonic treatment until the diphenylcarbazide is completely dissolved, then transfer to a 250 mL volumetric flask and add ultrapure water to make up to 250 mL. The test was analyzed by UV-visible spectrometer, and the maximum absorbance was obtained at λ=544 nm. The degradation efficiency is determined by C t / C0 judgment, C t is the instantaneous concentration of the solution, and C0 is the initial solution concentration. The specific calculation formula is as follows: η=C t / C0×100%.
[0049] Embodiment 3:
[0050] At room temperature, 4 portions of 50 mL of a 100 mg / L K2Cr2O7 solution (solvent: deionized water) were taken, and the pH was adjusted to 3 with a hydrochloric acid solution. 50 mg of NPTS, NPTS@PANI-15, NPTS@PANI-50, and NPTS@PANI-100 prepared in Example 1 were weighed respectively, stirred for 30 minutes in the dark to reach adsorption-desorption equilibrium, and a 300 W xenon lamp equipped with a 420 nm filter was turned on to perform a photocatalytic reduction of Cr(VI) under visible light irradiation. 1 mL of the reacted solution was added to the developer prepared in Example 2, and the Cr(VI) concentration was analyzed using an ultraviolet-visible spectrometer. Figure 6The catalytic activity of NPTS, NPTS@PANI-15, NPTS@PANI-50 and NPTS@PANI-100 under acidic conditions was demonstrated. At pH=3, NPTS@PANI-15 can completely reduce 100 mg / L of Cr(VI) within 10 minutes. The photocatalytic activity of NPTS crystals is low, and about 15% of Cr(VI) is still not reduced after 30 minutes of illumination. The reduction rate of Cr(VI) by NPTS@PANI-50 within 30 minutes reaches 99.4%, while the reduction rate of Cr(VI) by NPTS@PANI-100 within 30 minutes is 86.7%. By comparing with the commercially available P25, the catalyst concentration used is 1g / L. When reducing 100 mg / L of Cr(VI), P25 can only reduce to 10% within 10 minutes. Compared with NPTS@PANI-15, the Cr(VI) reduction performance of P25 is 90 times worse. Compared with the catalyst CdS@ZnIn2S4 reported in the literature, the performance of NPTS@PANI-15 is 6 times that of CdS@ZnIn2S4.
[0051] Embodiment 4:
[0052] At room temperature, 50 mL of 100 mg / L K2Cr2O7 solution (solvent is deionized water) was measured, and its pH was adjusted to 2, 3, 5, 7 and 9 respectively with hydrochloric acid solution or sodium hydroxide solution. 50 mg of NPTS@PANI-15 prepared in Example 1 was weighed and added to the above solution, stirred for 30 minutes in the dark to reach adsorption-desorption equilibrium, and a 300 W xenon lamp equipped with a 420 nm filter was turned on to perform a photocatalytic reduction of Cr(VI) experiment under visible light irradiation. 1 mL of the reacted solution was added to the developer prepared in Example 2, and the Cr(VI) concentration was analyzed using a UV-visible spectrometer.
[0053] Figure 7The catalytic activity of the product under acidic, neutral and alkaline conditions was demonstrated. At pH = 2, the reduction rate of Cr(VI) by catalyst NPTS@PANI-15 reached 98.4% after 5 minutes of illumination, and reached 100% after 10 minutes. At pH = 3, the reduction rate of Cr(VI) by catalyst NPTS@PANI-15 reached 85.3% after 5 minutes of illumination, and reached 100% after 10 minutes. Obviously, the lower the pH value, the stronger the acidity, and the faster the reduction rate. At pH = 5, the reduction rate of Cr(VI) by catalyst NPTS@PANI-15 reached 100% after 20 minutes of illumination. At pH = 7, the reduction rate of Cr(VI) by catalyst NPTS@PANI-15 reached 89.8% after 30 minutes of illumination. At pH = 9, the reduction rate of Cr(VI) by catalyst NPTS@PANI-15 was only 35.8% after 30 minutes of illumination. This indicates that high pH has a significant inhibitory effect on the photocatalytic reduction of Cr(VI) by catalyst NPTS@PANI-15.
[0054] Embodiment 5:
[0055] At room temperature, 50 mL of K2Cr2O7 solution (solvent is deionized water) of different concentrations (50, 100, 150, 200 mg / L) was measured, and the pH was adjusted to 3 with hydrochloric acid solution. Subsequently, 50 mg of NPTS@PANI-15 prepared in Example 1 was added to the above solution, and stirred for 30 minutes in the dark to reach adsorption-desorption equilibrium. Then, a 300W xenon lamp equipped with a 420nm filter was turned on, and a photocatalytic reduction of Cr(VI) experiment was carried out under visible light irradiation. 1 mL of the reacted solution was added to the developer prepared in Example 2, and the Cr(VI) concentration was analyzed using a UV-visible spectrometer.
[0056] Figure 8 The product demonstrates its catalytic reduction activity for different concentrations of Cr(VI) in an acidic environment. The product can completely reduce 50mg / L Cr(VI) within 5 minutes, 100mg / L Cr(VI) within 10 minutes, and 150mg / L Cr(VI) within 15 minutes. It can completely reduce 200mg / L Cr(VI) within 20 minutes. It can reduce 300mg / L Cr(VI) by 75% within 30 minutes.
[0057] Embodiment 6:
[0058] At room temperature, 3 portions of 50 mL of a 100 mg / L K2Cr2O7 solution (solvent: deionized water) were taken and the pH was adjusted to 3 with a hydrochloric acid solution. Different doses (10, 50, 100 mg) of NPTS@PANI-15 prepared in Example 1 were weighed and added to the above solution, and stirred for 30 minutes in the dark to reach adsorption-desorption equilibrium. Then, a 300W xenon lamp equipped with a 420nm filter was turned on, and a photocatalytic reduction of Cr(VI) experiment was carried out under visible light irradiation. 1 mL of the reacted solution was added to the developer prepared in Example 4, and the Cr(VI) concentration was analyzed using a UV-visible spectrometer.
[0059] Embodiment 7:
[0060] At room temperature, 50 mL of 100 mg / L K2Cr2O7 solution (solvent is deionized water) was measured and its pH was adjusted to 3 with hydrochloric acid solution. 50 mg of NPTS@PANI-15 prepared in Example 1 was weighed and added to the above solution, and stirred for 30 minutes in the dark to reach adsorption-desorption equilibrium. Then, a 300W xenon lamp equipped with a 420nm filter was turned on, and a photocatalytic reduction of Cr(VI) experiment was carried out under visible light irradiation. 1 mL of the reacted solution was added to the developer prepared in Example 4, and the Cr(VI) concentration was analyzed using an ultraviolet-visible spectrometer. The reacted NPTS@PANI-15 was washed twice with a pH=2.5 nitric acid solution, ultrapure water, and anhydrous ethanol, respectively, and dried. The above process was repeated with the dried product, which was the second cycle test. By analogy, a total of 5 cycle tests were carried out to verify the reusability of the product. Fig.10 The product demonstrated excellent cycle stability.
[0061] Embodiment 8:
[0062] At room temperature, 50 mL of a 100 mg / L K2Cr2O7 solution (the solvents were tap water, water from Nanjing Xuanwu Lake, and water from the Yangtze River in Nanjing) was measured and its pH was adjusted to 3 with a hydrochloric acid solution. 50 mg of NPTS@PANI-15 prepared in Example 1 was weighed and added to the above solution, stirred for 30 minutes in the dark to reach adsorption-desorption equilibrium, and a 300 W xenon lamp equipped with a 420 nm filter was turned on to perform a photocatalytic reduction of Cr(VI) under visible light irradiation. 1 mL of the reacted solution was added to the developer prepared in Example 2, and the Cr(VI) concentration was analyzed using an ultraviolet-visible spectrometer.
[0063] Fig.12 It was demonstrated that the product can still exhibit high catalytic activity in tap water, water from Nanjing Xuanwu Lake, and water from the Yangtze River in Nanjing.
[0064] Example 9
[0065] 50 mL of 100 mg / L K2Cr2O7 solution (solvent is deionized water) was measured and its pH was adjusted to 3 with hydrochloric acid solution. 50 mg of NPTS@PANI-15 prepared in Example 1 was weighed and added to the above solution, and stirred for 30 minutes in the dark to reach adsorption-desorption equilibrium. Subsequently, a photocatalytic reduction of Cr(VI) was carried out under sunlight, and the experimental environment temperature was 38°C. 1 mL of the reacted solution was added to the developer prepared in Example 4, and the Cr(VI) concentration was analyzed using a UV-visible spectrometer. Fig.13 The product was shown to exhibit high catalytic activity under sunlight.
Claims
1. A method for preparing a composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI, characterized in that: Here are the steps: (1) Add tin tetrachloride pentahydrate, nickel chloride hexahydrate, selenium powder, and o-phenanthroline to a mixed solution of dimethylamine aqueous solution and ultrapure water, transfer the mixture to a reactor, heat it, cool it, wash it, and dry it to prepare [Ni(phen)3][Sn3Se7]·1.5H2O, named NPTS, which is ground and set aside; (2) NPTS crystal powder is dispersed in an acidic aqueous solution and stirred evenly, which is recorded as dispersion A. (3) Dissolve aniline in an acidic aqueous solution and stir evenly, which is referred to as solution B. (4) Slowly pour dispersion A into solution B to form a red suspension C; (5) Pour ammonium persulfate into the acidic aqueous solution, dissolve it under ultrasonication, and then pour it into the red suspension C; (6) After pouring, the suspension is placed in an ice-water mixture and stirred in an ice bath; after centrifugation, washing, and drying, a composite material NPTS@PANI is obtained, where PANI is polyaniline.
2. The method for preparing the composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI according to claim 1, characterized in that: The synthesis method of NPTS in step (1) is as follows: 0.51 mmol, 0.178 g SnCl4·5H2O, 0.52 mmol, 0.124 g NiCl2·6H2O, 2.10 mmol, 0.166 g Se and 1.54 mmol, 0.278 g o-phenanthroline are added to a mixed solution of 3 mL, 40 wt% dimethylamine aqueous solution and 1 mL H2O; the mixture is sealed in a 25 mL reactor and reacted at 190 ºC for 5 days; cooled to room temperature, the product is washed with ethanol and water for multiple times and dried to obtain dark red block crystals of NPTS.
3. The method for preparing the composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI according to claim 1, characterized in that: The grinding method of the NPTS powder in step (1) is as follows: take 0.05 g of NPTS crystals, add 2 mL of anhydrous ethanol, and grind until the anhydrous ethanol is completely evaporated.
4. The method for preparing the composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI according to claim 1, characterized in that: Aniline monomer was used as a precursor and ammonium persulfate was used as an oxidant to in-situ coat polyaniline on the surface of NPTS. The pH value of the acidic solution used in the composite process was 2.
5.
5. The method for preparing the composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI according to claim 4, characterized in that: The specific steps of in-situ coating of polyaniline are as follows: (1) Pour 0.2 g of NPTS powder into 30 mL of ultrapure water, adjust the pH to 2.5 with hydrochloric acid solution, and stir for 10 min to obtain dispersion A. (2) Pour a certain amount of aniline into 10 mL of ultrapure water, adjust the pH to 2.5 with hydrochloric acid solution, and stir for 10 min to obtain solution B; (3) Slowly pour dispersion A into solution B and continue stirring for 30 min to obtain a red suspension C. (4) Take a certain amount of ammonium persulfate and dissolve it in 30 mL of hydrochloric acid solution, the pH of the solution is 2.5; (5) Using a smart syringe, 30 mL of ammonium persulfate solution was dripped into the red suspension C at a flow rate of 0.4 mL / min. The entire reaction system was placed in an ice bath and reacted for 10 h. After centrifugation, the suspension was washed twice with ultrapure water and anhydrous ethanol in sequence and dried in a vacuum oven at room temperature for 12 h to obtain brown powder NPTS@PANI.
6. The method for preparing the composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI according to claim 5, characterized in that: The amounts of aniline used were 15 μL, 50 μL, and 100 μL, respectively, and the corresponding products were NPTS@PANI- x , x = 15, 50, 100; the amounts of ammonium persulfate required for the above three products are 0.076 mg, 0.253 mg, and 0.506 mg, respectively.
7. A method for photocatalytic reduction of Cr(VI) using the composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI prepared by the method according to claim 6, characterized in that: Pretreated composite material NPTS@PANI- x , x = 15, 50, 100 were applied to the photocatalytic reduction of Cr(VI).
8. The use of the composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI according to claim 7, characterized in that: The pretreatment process is as follows: 50 mg NPTS@PANI- x , x = 15, 50, 100 were added into 50 mL ultrapure water at pH = 2.0 and stirred for 30 min.
9. Use of the composite material [Ni(phen)3][Sn3Se7]·1.5H2O@PANI according to claim 8, characterized in that: Take the obtained pretreated material 50 mg NPTS@PANI- x , x = 15, 50, 100 Photocatalytic reduction of K2Cr2O7 solution at pH = 3, with a K2Cr2O7 concentration of 100 mg / L.
